An Astute Ganne Optimized MPPT Controller Combined with High Gain Interleaved Boost Converter for Grid-PV Systems - Palanichamy, Priya; Krishnasamy, Rajesh; Loretta, G. Irin; M J, Carmel Mary Belinda; Gomathi, S. (2023 7th International Conference on Electronics, Communication and Aerospace Technology (ICECA), 2023)
Due to the rising need for energy, getting the most electricity possible from solar Photovoltaic (PV) systems is one of the most significant tasks. As a result, the previous research works develop several forms of Maximum Peak Point Tracking (MPPT) controlling systems. Due to its precise solution and quick convergence, intelligent optimization-based MPPT techniques are frequently used in numerous works. The modelling of a complicated system required more effort, had a higher error rate, and required incorrect tracking, which posed adverse effects. Therefore, the proposed work aims to design a cutting-edge controlling and converter models for grid-PV systems. In the previous work, the solar panel coating is performed with the use of Silver Nano-Particles (AgNPs) for maximizing the power tracking efficiency. In this instance, an Improved Ganne Optimization (IGO) - MPPT controlling model is used to determine the MPP under various operating situations with improved voltage, current and power current characteristics. In addition, a high gain interleaved boost converter has been used to regulate the output DC voltage to its maximum potential. The adoption of voltage source inverter and LCL filtering circuit models also ensures that grid-PV systems provide power of higher quality. Finally, a number of parameters are used to validate the simulation findings and the outcomes of the proposed controlling model.